1961
DOI: 10.1084/jem.114.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Tubercle Bacillus-Monocyte Relationship

Abstract: There are various observations to indicate that under appropriate conditions of in vitro cultivation, attenuation of virulent tubercle bacilli may be achieved.The BCG strain of tubercle bacillus, originally a virulent bacillus of the bovine type, provides a classical example of in v/tro attenuation after prolonged cultivation on a glycerol-potato-bile medium (1). Similar reductions of bacillary virulence have also been accomplished by cultivation of virulent forms at low hydrogen ion concentrations (2, 3) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1961
1961
1969
1969

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In fact, Fong, Chin, and Elberg (1961) have recently demonstrated a series of changes which are impressed upon mycobacteria when they are passed directly through generations of intramonocytic growth. Losses in mouse lethality, neutral red binding, increased sensitivity to sodiumn oleate, among others, were determined.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Fong, Chin, and Elberg (1961) have recently demonstrated a series of changes which are impressed upon mycobacteria when they are passed directly through generations of intramonocytic growth. Losses in mouse lethality, neutral red binding, increased sensitivity to sodiumn oleate, among others, were determined.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tissue culture methods (2,3) has yielded more controversial findings, but one of these earlier studies (2) appeared to confirm Lurie's conclusions concerning acquired cellular resistance. Our own investigations involving in vitro cultures of infected histiocytes have shown that peritoneal exudate cells of normal and immunized rabbits could modify virulent tubercle bacilli, thereby reducing bacillary virulence for mice and inducing changes in certain other bacterial attributes (4). Although these modifications of virulent tubercle bacilli occurred after interaction of bacilli with either normal or immune histiocytes, only immune histiocytes were able to alter virulent tubercle bacilli to the extent where they lost the ability to necrotize the histiocytes themselves (5); this latter observation may be indicative of a greater capacity of immune histiocytes to modify bacillary virulence.…”
mentioning
confidence: 99%
“…Detailed descriptions of procedures and materials used in these studies have been described in earlier reports (1)(2)(3)(4)(5)(6) and are therefore briefly described herein.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of Passaged Bacter/~.--The preparation of virulent tubercle bacilli which had been grown in immune histiocytes has been described in an earlier paper (6). The same methods were used in the present studies except that virulent H37Rv were grown in Brucdla-lmmune hlstiocytes rather than BCG-immune histiocytes.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%